2007
DOI: 10.1038/labinvest.3700599
|View full text |Cite
|
Sign up to set email alerts
|

Midkine is involved in tubulointerstitial inflammation associated with diabetic nephropathy

Abstract: The concept that inflammation plays a crucial role in the pathogenesis of diabetic nephropathy has been recently emerging, although the principal pathology of diabetic nephropathy comprises glomerular sclerosis and associated changes in nephrons. Here, we identified the growth factor midkine (MK) as a novel key molecule involved in inflammation associated with Streptozotocin-induced diabetic nephropathy. The tubulointerstitial damage, as assessed as morphological changes, osteopontin expression, collagen I dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 32 publications
3
77
0
Order By: Relevance
“…It may play a role in recruitment of neutrophils and macrophages into inflamed tissue (23,24), and up-regulation of synthesis of inflammatory mediators (25)(26)(27). Animal studies have revealed that several inflammation-related phenomena were substantially alleviated in midkine-deficient animals (12,25,(28)(29)(30)(31)(32). The mechanisms mentioned above may also operate in the involvement of midkine in the pathogenesis of UC since the accumulation of neutrophiles and monocytes associated with aberrant inflammatory response is essential for development of UC (14).…”
Section: Discussionmentioning
confidence: 99%
“…It may play a role in recruitment of neutrophils and macrophages into inflamed tissue (23,24), and up-regulation of synthesis of inflammatory mediators (25)(26)(27). Animal studies have revealed that several inflammation-related phenomena were substantially alleviated in midkine-deficient animals (12,25,(28)(29)(30)(31)(32). The mechanisms mentioned above may also operate in the involvement of midkine in the pathogenesis of UC since the accumulation of neutrophiles and monocytes associated with aberrant inflammatory response is essential for development of UC (14).…”
Section: Discussionmentioning
confidence: 99%
“…38 Briefly, the renal cortex divided from the medulla was resolved with collagenase (Wako Chemicals, Miyazaki, Japan) and the lysate was then filtered through 38-m strainer, using a mesh sieving method. The fluid was centrifuged to pellet the various renal cells, which were plated with cultured media for 1 hour of incubation.…”
Section: Cell Culturementioning
confidence: 99%
“…144 In a mouse model of IRI, it was found that MK levels were increased threefold in proximal tubular cells, leading to neutrophil recruitment and resulting in an inflammatory reaction and tubulointerstitial damage. 143 It was believed that superoxide anions produced during the IRI procedure led to the upregulation of MK, and it is feasible that MK expression could be altered during CI-AKI.…”
mentioning
confidence: 99%